Kiai, Pesantren, dan Tantangan Masyarakat Multikultural - Syamhuri, M. Rijal Risalam (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
This article discusses the challenges of a multicultural Indonesian society where this diversity is vulnerable to friction and division. As for the reality, there are educational institutions that are able to stem this diversity into a strategy for the formation of human resources who are ready to face the challenges of globalization that know no national borders. Pesantren is a heterogeneous environment in which students come from various races, cultures, social strata of society, economic backgrounds with various individual characters. The kiai, as role models and central figures in the pesantren, need to first turn on the multicultural values ​​in them, which then together with all pesantren residents live the multicultural values ​​in the pesantren. The kiai's example becomes a strategic educational method in forming students who are critical and open to progress and can participate in forming a society that thinks positively about diversity.